2012
DOI: 10.1021/ma3001324
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Free Volume Characteristics of Composite Membranes Fabricated through Static and Dynamic Interfacial Polymerization Processes

Abstract: For fabricating a polyamide (PA) selective film by interfacial polymerization (IP), we selected a linear structure of succinyl chloride, an acyl chloride monomer, and of 1,3-diaminopropane, an amine monomer. It was not by conventional IP; instead, the technique of spin-coating was successfully integrated into the process of IP. We called such integrated systems as dynamic IP. Spin-coating provided a strong centrifugal force which induced arrangement and orientation of molecular chains in the horizontal directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 35 publications
5
28
1
Order By: Relevance
“…Based on TEM images of the active layer of a brackish water reverse osmosis (RO) membrane in which globular features 20-60 nm in size were visible, Pacheco et al further proposed that active layers are composed of a dense nodular base from which the ridge-and-valley structure extends outwards. Similar features to those interpreted as nodules by Pacheco et al and voids by others [13][14][15][16] are visible in TEM images reported elsewhere [18][19][20], although they were not identified as nodules or voids.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on TEM images of the active layer of a brackish water reverse osmosis (RO) membrane in which globular features 20-60 nm in size were visible, Pacheco et al further proposed that active layers are composed of a dense nodular base from which the ridge-and-valley structure extends outwards. Similar features to those interpreted as nodules by Pacheco et al and voids by others [13][14][15][16] are visible in TEM images reported elsewhere [18][19][20], although they were not identified as nodules or voids.…”
Section: Introductionsupporting
confidence: 86%
“…For each membrane, the region corresponding to the active layer is outlined in red dotted lines. For all membranes, the TEM images show well-defined globular features, lighter in color than the surrounding polyamide, similar to the features identified as voids [13][14][15][16] and nodules [17] in the literature. The grayscale contrast between any two regions in TEM images is produced by the difference in the amount of electrons of the analysis beam that pass through the two regions of the sample [41].…”
Section: Water Permeation Testssupporting
confidence: 78%
See 1 more Smart Citation
“…The parameters commonly studied are the concentrations of amine and/or acyl chloride reactants, contact time between the two reactants [9][10][11], and annealing temperature and time [12,13]. In another approach, the surface coating method has also been used to fabricate membranes, and spin-coating is shown to be more favorable than a simple dip-coating for fabricating a thin layer with a dense structure [14]. To overcome the problems related to solvent-induced swelling of the membranes, inorganic components, cross-linkers or nanoparticles, may be introduced into the polyamide skin layer during interfacial polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, membrane fabrication methods like interfacial polymerization, plasma polymerization, atom transfer radical polymerization (ATRP), dip-coating and also other methods have been applied to the preparation of ultrathin pervaporation membranes. [22][23][24][25] It can be concluded that the dramatic decrease of selective layer thickness has been achieved mostly because small molecules are used instead of polymers, like PDMS, as lm forming monomers in most of these methods. Therefore, in our previous study, Zhang et al 26 have reported the preparation of thin high-ux poly(vinyltriethoxysilane) (PVTES) membranes with vinyltriethoxysilane (VTES) monomers for ethanol recovery, which possessed a ux over 10 000 g m À2 h…”
Section: Introductionmentioning
confidence: 99%